2020
DOI: 10.1038/s41586-020-2894-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial connectivity matches direction selectivity in visual cortex

Abstract: The selectivity of neuronal responses arises from the architecture of excitatory and inhibitory connections. In primary visual cortex, the selectivity of layer 2/3 neurons for stimulus orientation and direction is thought to arise from similarly-selective intracortical inputs 1 – 7 . A neuron’s excitatory inputs, however, can have diverse stimulus preferences 1 – 4 , 6 – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 66 publications
7
152
1
Order By: Relevance
“…These data were well fit by the Gaussian model (Fig 2A, solid red line) and indicated low peak connectivity among excitatory cells (~5%), moderate connectivity rates among inhibitory cells (~11%), and higher connectivity across E-I cell classes (E→I 12%, I→E 15%). In a rabies tracing study of primary visual cortex L2/3, E→E connections were found to have a wider lateral extent compared to I→E (28) . We confirm this result and additionally find that E→E and I→I connections have a similar spatial extent that is larger than both E→I and I→E connections.…”
Section: Distance Dependence Of Connectivitymentioning
confidence: 87%
“…These data were well fit by the Gaussian model (Fig 2A, solid red line) and indicated low peak connectivity among excitatory cells (~5%), moderate connectivity rates among inhibitory cells (~11%), and higher connectivity across E-I cell classes (E→I 12%, I→E 15%). In a rabies tracing study of primary visual cortex L2/3, E→E connections were found to have a wider lateral extent compared to I→E (28) . We confirm this result and additionally find that E→E and I→I connections have a similar spatial extent that is larger than both E→I and I→E connections.…”
Section: Distance Dependence Of Connectivitymentioning
confidence: 87%
“…Similarly, the spatial position (in terms of retinotopic coordinates) of inhibitory neurons that are presynaptic to a direction-selective neuron is offset relative to that of its presynaptic excitatory neurons. This spatial offset predicts the preferred direction of the direction-selective neuron (Rossi et al 2020).…”
Section: Direction Selectivitymentioning
confidence: 96%
“…This applies to both feedforward connectivity from L4 to L2/3 and recurrent connectivity within L2/3. Panel a adapted from Ko et al (2011), Lee et al (2016), Lien & Scanziani (2013), Morgenstern et al (2016), Rossi et al (2020), Wertz et al (2015), and Yoshimura et al (2005). (b) The spatial organization of connectivity is coaxial, whereby a neuron (red) tends to receive input from neurons (green) with similar orientation preference and whose location, in retinotopic coordinates, is along the axis of their preferred orientation.…”
Section: Computations By Recurrent Excitationmentioning
confidence: 99%
“…64 Recent evidence shows a V1 neuron receives spatially offset inputs from excitatory and inhibitory neuron populations in agreement with its direction selectivity. 65 In carnivores and primates, the simple cell subunits also have a push-pull structure. 2729 Similarly, T5 neurons show a contrast-opponent organization ( Fig.…”
Section: Discussionmentioning
confidence: 99%